A New Research Direction of Authentic Leadership in the Field of Adult Education - Jihye Oh; Soo Jeoung Han (Adult Education Research Conference, 2017)
This research reviewed authentic leadership and learning-related outcomes at workplace from the perspective of adult education/learning. Over the past decade, authentic leadership has been investigated only from performance-oriented perspective at workplace, despite its learning-oriented concept and component. Therefore, this research provided new insight and direction into the field of adult education/learning at workplace through integrated literature review of authentic leadership.
Keywords: authentic leadership; adult learning; workplace